Desk numeration system using image processing / Siti Rozanae Ismail … [et al.] - Ismail, Siti Rozanae; Ibrahim, Ireen Munira; Najmuddin, Ahmad Farid; A Tambi, Abdul Malek; Dzulkurnain, Nurliana Aqiiah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Image is an important record of our lives. At the earlier stage of the introduction of image, it is used to record memorable moment. As the technology becomes increasingly advanced, the uses of image become widespread especially in image processing. Many people having some problems to count the number of desk or object in the classroom in a short time. They have to count the entire desk one by one. They have to calculate manually the number of desk that needs to be added or removed. Sometimes, they will make mistakes in counting the number of desk. In this case, the time taken to calculate the number of desk will be longer and it will cause them to take a long time to recalculate it. Therefore, this system is designed to overcome these problems by using image processing technique. This paper is describing about Desk Numeration System Using Image Processing. The aim for this prototype system is to count the number of desk using image processing technique, and to develop a prototype system that can automatically count the number of desk. The images are taken from the models that are developed and captured using a digital camera. There are several steps used to detect and count desk such as converting images, filtering images, edge detector, Hough Transform, and counting. This prototype system is using C++ language, MATLAB software and some mathematical formulas. The result for detect and count the number of desk is tested and recorded. In conclusion, image processing in the best technique for detects and recognize object.